A qualitative assessment of the preliminary food-based dietary guidelines for infants 6-12 months of age in the greater Oudtshoorn area - Van der Merwe, Julanda (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MVoeding)--University of Stellenbosch, 2004.